Methodological Aspects of the Problems of Modern School Management - Voronov M.V; Baykov S.V (Moscow State University of Psychology and Education, 2020)
The materials reflecting the authors' study on the problems of improving the activities of the modern school are presented. Based on the analysis of the emerging new labor structure of society, a generalized system of modern education is proposed. The key place allocated to it in the system of general education is emphasized. The main problems of the modern secondary school in general and the management of its activities in particular are considered. The main attention is paid to the formation of the ranking of schools, which includes indicators of diverse characteristics. It is proposed to consider the educational institution as a social system, within the framework of which the students develop skills of behavior, relationships in the team and with the external environment. It is noted that in each educational institution, an internal organizational and psychological culture is formed, which leaves its mark on almost all the processes taking place there, in particular, it creates restrictions on the possibility of making certain decisions and the likelihood of their implementation. This position necessitates the formation of a school-specific system of consistent indicators, including a number of qualitative indicators. The use of such indicators in school management processes necessitates the development of specialized methods for assessing the effectiveness of its activities. The article proposes a method for assessing qualitative characteristics, providing an increase in their level of objectivity.